Fucoxanthin Enhances Cisplatin-Induced Cytotoxicity via NFκB-Mediated Pathway and Downregulates DNA Repair Gene Expression in Human Hepatoma HepG2 Cells - Liu, Cheng-Ling (MDPI, 2013)
Cisplain, a platinum-containing anticancer drug, has been shown to enhance DNA repair and to inhibit cell apoptosis, leading to drug resistance. Thus, the combination of anticancer drugs with nutritional factors is a potential strategy for improving the efficacy of cisplatin chemotherapy. In this study, we investigated the anti-proliferative effects of a combination of fucoxanthin, the major non-provitamin A carotenoid found in Undaria Pinnatifida, and cisplatin in human hepatoma HepG2 cells. We found that fucoxanthin (1–10 μΜ) pretreatment for 24 h followed by cisplatin (10 μΜ) for 24 h significantly decreased cell proliferation, as compared with cisplatin treatment alone. Mechanistically, we showed that fucoxanthin attenuated cisplatin-induced NFκB expression and enhanced the NFκB-regulated Bax/Bcl-2 mRNA ratio. Cisplatin alone induced mRNA expression of excision repair cross complementation 1 (ERCC1) and thymidine phosphorylase (TP) through phosphorylation of ERK, p38 and PI3K/AKT pathways. However, fucoxanthin pretreatment significantly attenuated cisplatin-induced ERCC1 and TP mRNA expression, leading to improvement of chemotherapeutic efficacy of cisplatin. The results suggest that a combined treatment with fucoxanthin and cisplatin could lead to a potentially important new therapeutic strategy against human hepatoma cells.